Cleaner production of lignocellulosic nanofibrils: Potential of mixed enzymatic treatment. (10th October 2020) - Bian, Huiyang; Chen, Lidong; Dong, Maolin; Fu, Yanqiao; Wang, Ruibin; Zhou, Xuelian; Wang, Xiu; Xu, Junhua; Dai, Hongqi
Abstract: Lignocellulosic nanofibrils (LCNF) production ordinarily requires vigorous chemical reactions and intensive mechanical fibrillation, causing potential environmental pollution. To overcome this issue, economic and green mixed enzymatic treatments were employed to prepare LCNF from unbleached pulp in this work. In contrast to mixed enzymatic post-treatment, pretreatment seems to be a better alternative for cellulose nanofibrillation, endowing LCNF with decreased average height (15.0 nm), higher shear storage modulus (387.3 Pa), and increased thermal stability with the maximal weight loss temperature (Tmax ) of 352 °C. The resultant LCNF was directly used to fabricate films without any chemical modification. It was found that the diameter of LCNF played key roles in affecting the surface morphology of film, for example, films made from fibrils with smaller diameter had smoother surface. Moreover, the tensile stress and Young's modulus of the resulting LCNF film prepared from pretreated fibrils were about 138% and 20% higher than those from post-treated fibrils. Overall, using mixed enzymes in addition to mechanical fibrillation, especially enzymatic pretreatment, is an environment-friendly method to prepare LCNF and films, which provides useful knowledge for low-cost and clean production and facilitates the commercialization and application of nanomaterials. Highlights: Cleaner production of LCNF was achieved by enzymatic treatment. Pretreatment was more suitable for cellulose nanofibrillation. Pretreatment endowed LCNF with higher viscoelasticity and better thermal stability. Films made from fibrils with small diameter presented higher mechanical properties. This work gives us insights into more efficient and reasonable enzymatic treatment.